Evaluating Generation Alpha Through the Lens of Organizational Practice - Srivastava, Babita (American Journal of Management, 2024)
In this paper, we use insights from OB and OT to analyze ways in which firms can help serve the needs of newly emergent organizational subjects and consumers. Our analysis is based on newly emergent demographics that differ from earlier generations in significant, non-trivial and unique ways. This presents both a threat and an opportunity to firms, as they search for consumers to satisfy and organizational subjects to deploy in the service of economic success. We identify ways in which firms can deploy demographic shifts to their advantage and identify ten emerging industry segments where these shifts will prove critical.